1994
DOI: 10.1557/jmr.1994.1973
|View full text |Cite
|
Sign up to set email alerts
|

A study of aluminum speciation in aluminum chloride solutions by small angle x-ray scattering and 27Al NMR

Abstract: Aluminum ions may exist in one of several different types of polynuclear species depending upon the degree to which it is hydrolyzed. The hydrolysis of aluminum can be explained by a metastable equilibrium among A1(H2O)6+, Al(OH)(H2O)s+, Al13O4(OH)24(H2O)i2f, and an oligomer. We have made small angle x-ray scattering and 27Al NMR measurements on 0.3 M aluminum chloride solutions over a range of OH/A1 ratios. 27A1 NMR shows two sharp peaks corresponding to the monomer A1(H2O)6+ and the tetrahedrally coordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 33 publications
(11 reference statements)
4
54
0
1
Order By: Relevance
“…Keggin-Al 13 Singhal and Keefer [7], Pophristic et al [21] assigned Al un formed at lower OH/Al ratios to the six-member-ring Al 6 (Al 6 (OH) 12 6+ ) species. Seichter et al [22], Allouche et al [23] reported the existence of Al 6 -type polycation [Al 13 (OH) 24 include various polymers and species with the structure of octahedrons arrayed similar to the six-member-ring style ( 2 -OH, 3 -OH).…”
Section: The Structural Difference Between Al 6 -Type Series Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Keggin-Al 13 Singhal and Keefer [7], Pophristic et al [21] assigned Al un formed at lower OH/Al ratios to the six-member-ring Al 6 (Al 6 (OH) 12 6+ ) species. Seichter et al [22], Allouche et al [23] reported the existence of Al 6 -type polycation [Al 13 (OH) 24 include various polymers and species with the structure of octahedrons arrayed similar to the six-member-ring style ( 2 -OH, 3 -OH).…”
Section: The Structural Difference Between Al 6 -Type Series Andmentioning
confidence: 99%
“…However, benefiting from the advanced instrumentation the situation is subject to change. Singhal and Keefer [7] by small angle X-ray scattering and Pophristic et al [21] by molecular dynamics demonstrated the existence of the six-member-ring hexamer species in the hydroxyl-Al solution. Moreover, Seichter et al [22] reported that some crystal solid of [Al 13 (OH) 24 [23] reexamined it later with 2D 27 Al 3QMAS NMR and referred to polycation as Mögel-Al 13 15+ .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unlike the Al 13 species of Keggin structure, these oligomers often do not have Keggin structure and are undetectable with 27 Al NMR spectroscopy. As the hydroxyl Al speciation results proposed by Singhal and Seichter, these species might be composed of six member ring structure [5,16]. It can also be inferred from above experimental results that these species might be formed without strict synthesis condition and thus could decompose easily into monomers or polymers with lower polymerization degree.…”
Section: Effect Of Aging Temperature On Transformation Of Al Speciesmentioning
confidence: 55%
“…Thus, many researchers have put emphasis on the transformation process of Al 13 in hydroxyl Al solution under various aging conditions [12][13][14][15]. In fact, besides Al 13 , some other polymers have also been proved to exist in solution by chemical calculation methods and instrumental characterization [16,17]. In our previous studies, Al 13 and some other polymeric Al species have been proved to coexist in hydroxyl Al solutions, especially the solutions with lower basicity [18].…”
Section: Introductionmentioning
confidence: 97%